Fatty acids from edible sea hares: anti-inflammatory capacity in LPS-stimulated RAW 264.7 cells involves iNOS modulation. Issue 12 (11th February 2015) - Pereira, R. B.; Taveira, M.; Valentão, P.; Sousa, C.; Andrade, P. B.
<x xml:space="preserve">Abstract</x> The inclusion of marine organisms in the diet is gaining importance due to their richness in health beneficial nutrients.